Human Pituitary Organoids: Transcriptional Landscape Deciphered by scRNA‐Seq and Stereo‐Seq, with Insights into SOX3's Role in Pituitary Development - Shengjie Wang; Deyue Jiang; Yan Xiao; Qiaozhen Qin; Heyang Zhang; Lingtong Ye; Jide Jin; Xiaoxia Jiang; Qinghua Guo (Advanced Science)
Abstract The 3D human pituitary organoid represents a promising laboratory model for investigating human pituitary diseases. Nonetheless, this technology is still in its nascent stage, with uncertainties regarding the cellular composition, intercellular interactions, and spatial distribution of the human pituitary organoids. To address these gaps, the culture conditions are systematically adjusted and the efficiency of induced pluripotent stem cells’ (iPSCs’) differentiation into pituitary organoids is successfully improved, achieving results comparable to or exceeding those of previous studies. Additionally, single‐cell RNA‐sequencing (scRNA‐seq) and stereomics sequencing (Stereo‐seq) are performed on the pituitary organoids for the first time, and unveil the diverse cell clusters, intricate intercellular interactions, and spatial information within the organoids. Furthermore, the SOX3 gene interference impedes the iPSCs’ differentiation into pituitary organoids, thereby highlighting the potential of pituitary organoids as an ideal experimental model. Altogether, the research provides an optimized protocol for the human pituitary organoid culture and a valuable transcriptomic dataset for future explorations, laying the foundation for subsequent research in the field of pituitary organoids or pituitary diseases.